OPTIMIZATION OF PROTOPLAST ISOLATION FROM DIFFERENT TYPES OF SAMPLES - Mose, Windi; Wael, Syahran (RUMPHIUS, 2024)
Isolation of protoplasts in several plant species still requires optimization to produce protoplasts that are viable and can be used for further analysis. This research aims to optimize protoplast isolation protocols in several plants: Orchid Dendrobium macrocarpus, potato Solanum tuberosum, and microalgae Phaeodactylum tricornutum, Botryococcus braunii, and Spirulina sp. The results showed that in vitro explant selection had higher sample uniformity, and a combination of enzyme solutions could be used to increase the effectiveness of protoplast isolation on D. macrocarpus, S. tuberosum, and Spirulina sp. This study provides information about protoplast isolation techniques and testing their viability as an attempt for plant breeding through micropropagation.